PENGARUH MULTIMEDIAAURORA 3 DIMENSI PRESENTATION TERHADAP MOTIVASI BELAJAR SISWA PADA MATA PELAJARAN EKONOMI DI SMA NEGERI 1 PALEMBANG - Angga Puja Kesuma; Djahir Basir; Rusmin AR (Jurnal PROFIT: Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2016)
The formulation of problem for this research is “what is the different of Aurora 3 Dimention Presentation impact with powerpoint multimedia impact against the studying student motivation in learning economic at high school of number one palembang ?”. This research is the kind of experiment research. Samples are taken to the tune of 80 students which have severally 40 students for control class and experiment class. The taking sample technique is cluster random sampling. The data accumulation techniques are observation and questionnaire. This research variables are Aurora 3 Dimention Presentation multimedia as the first free variable, powerpoint multimedia as the second free variable and the studying students motivation as the variable banded. This research subject is high school of number one palembang. The result of questionnaire data analysis mean before using Aurora 3 Dimention Presentation multimedia is 53,7% and The result of questionnaire data analysis mean after using Aurora 3 Dimention Presentation multimedia is 66,8%. Whereas, The result of questionnaire data analysis mean before using powerpoint multimedia is 53,5 % and The result of questionnaire data analysis mean after powerpoint multimedia is 63,7%. The result of hypothesis test is tcount = 2.0529 > ttables = 1,991 .So, there is the diference of Aurora 3 Dimention Presentation impact with powerpoint multimedia impact against the studying student motivation in learning economic at high school of number one palembang.